2019
DOI: 10.1051/e3sconf/20199704026
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of influence of heat-conducting inclusions on thermal protection of filler constructions of buildings

Abstract: Article represents recommendations on decrease in heat losses through heat-conducting inclusions of filler constructions of buildings. Recommendations are based on the analysis of calculations by a finite element method in software package Elcut. The purpose consists in the analysis of expediency of replacement of a steel reinforcement on glass composite reinforcement in design decisions of filler constructions in view of calculation of thermal fields. The way of decrease in the factor of cold bridges is resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous studies have shown the effect of heatconducting inclusions on the thermal protection of buildings. [14,15] Calculation of the temperature fields of external walls with hinged facade systems for the climatic conditions of Abakan is shown on Fig. 4, 5.…”
Section: Fig 3 Contamination Of the Moisture-windproof Membrane During Operationmentioning
confidence: 99%
“…Previous studies have shown the effect of heatconducting inclusions on the thermal protection of buildings. [14,15] Calculation of the temperature fields of external walls with hinged facade systems for the climatic conditions of Abakan is shown on Fig. 4, 5.…”
Section: Fig 3 Contamination Of the Moisture-windproof Membrane During Operationmentioning
confidence: 99%